Sustained increases in antibiotic prescriptions per primary care consultation for upper respiratory tract infections in England during the COVID-19 pandemic. Issue 1 (11th February 2023) - Yang, Zheyuan; Bou-Antoun, Sabine; Gerver, Sarah; Cowling, Thomas E; Freeman, Rachel
Abstract: Background: The responsible use of existing antimicrobials is essential in reducing the threat posed by antimicrobial resistance (AMR). With the introduction of restrictions during the COVID-19 pandemic, a substantial reduction in face-to-face appointments in general practice was observed. To understand if this shift in healthcare provision has impacted on prescribing practices, we investigated antibiotic prescribing for upper respiratory tract infections (URTI) consultations Methods: We conducted an interrupted time-series analysis using patient-level primary care data to assess the impact of the COVID-19 pandemic on consultations and antibiotic prescribing for URTI in England. Results: We estimated an increase of 105.7 antibiotic items per 1000 URTI consultations (95% CI: 65.6–145.8; P < 0.001) after national lockdown measures in March 2020, with increases mostly sustained to May 2022. Conclusions: Overuse of antibiotics is known to be a driver of resistance and it is essential that efforts to reduce inappropriate prescribing continue subsequent to the COVID-19 pandemic. Further work should examine drivers of increased antibiotic prescribing for URTI to inform the development of targeted antibiotic stewardship interventions.